Chemical ecology and eco-physiology of the grain chinch bug, Macchiademus diplopterus (Distant) (Hemiptera: Lygaeidae: Blissidae), a phytosanitary pest of South African export fruit - Okosun, Olabimpe Olayem (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--Stellenbosch University, 2012.